Color Trend of Residential Houses in Denpasar City as a Sociopsychological Reflection of the Covid-19 Pandemic - I Putu Udiyana Wasista (Badan Riset dan Inovasi Daerah Provinsi Bali, 2021)
Purpose: This study aims to determine the psychological condition of the people in Denpasar City, seen from the phenomenon of the trend of choosing color paint for homes during the COVID-19 pandemic. Research method: The survey was conducted in 12 paint shops and buildings spread across Denpasar City. The method used is structured interviews. The research method is qualitative with descriptive presentation. The results of data mining were studied using color psychology theory. Results and discussion: Based on the results of the study, it shows that the choice of white and bright colors has implications for the desire of the community to create peaceful, calm, clean and pleasant conditions in their homes during the COVID-19 pandemic. Implication: The color selection implicitly shows the expectations of the people of Denpasar City. Hopes for a better future, which had rocked many sectors of life during the COVID-19 pandemic.